2012
DOI: 10.1186/1756-8722-5-49
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in primary diffuse large B-cell lymphoma of adrenal gland treated with rituximab-CHOP chemotherapy from the Consortium for Improving Survival of Lymphoma (CISL)

Abstract: BackgroundThe objective of this study was to identify prognostic factors for survival in patients with primary diffuse large B-cell lymphoma (DLBCL) of the adrenal gland.MethodsThirty one patients diagnosed with primary adrenal DLBCL from 14 Korean institutions and treated with R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone) were analyzed.ResultsComplete remission (CR) and overall response rate after R-CHOP chemotherapy were 54.8% and 87.0%. The 2-year estimates of overall surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 30 publications
4
88
1
8
Order By: Relevance
“…Before the introduction of Rituximab in the CHOP therapy, 20-50% of overall survival rate was reported in lymphomas patients. Data by Kim et al (11) revealed a complete response rate of 54.8% and partial response rate of 32.3% after the R-CHOP therapy (11). There is a high risk of CNS relapse in primary adrenal NHL, and the risk remains almost same even after the addition of R-CHOP therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Before the introduction of Rituximab in the CHOP therapy, 20-50% of overall survival rate was reported in lymphomas patients. Data by Kim et al (11) revealed a complete response rate of 54.8% and partial response rate of 32.3% after the R-CHOP therapy (11). There is a high risk of CNS relapse in primary adrenal NHL, and the risk remains almost same even after the addition of R-CHOP therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Ultrasound-guided biopsy is recommend for the differential diagnosis following the identification of low density of adrenal glands on CT scan images, and immunohistochemical examination further confirm the diagnosis and prognosis. The recommended treatment regimen for PAL is R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone), a classical chemotherapy regimen (20), with chemotherapy being the typical treatment. It has been reported that surgery is not recommended for treatment (21).…”
Section: Discussionmentioning
confidence: 99%
“…Based on univariate analysis, these authors also demonstrated that the lung, liver, spleen, kidney, and skin involvement was significant. Furthermore, isolated reports have suggested that involvement of the adrenal glands [21,22], skin [23], and kidney [24] may also be associated with a poor prognosis. Moreover, we showed that a novel extranodal scoring system, using these extranodal sites, may improve the predictability of older risk prediction models.…”
Section: Discussionmentioning
confidence: 99%